Pengaruh Kualitas Produk dan Kepercayaan Terhadap Keputusan Pembelian Melalui Minat Beli pada Pengguna E-Commerce Shopee (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta) - Henni Marito Siregar; Osly Usman (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of product quality and trust on purchasing decisions, with purchase intention serving as an intervening variable among Shopee e-commerce users; the study focuses on students from the Faculty of Economics and Business at the State University of Jakarta (FEB UNJ). An explanatory survey approach was employed, involving 116 respondents selected via purposive sampling. Data analysis was conducted using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method based on questionnaire data. The results indicate that all indicators met validity and reliability standards, with outer loadings ≥ 0.85, Cronbach's Alpha ≥ 0.928, and Composite Reliability ≥ 0.940. Path coefficients reveal that product quality positively influences purchase intention (β = 0.627), trust positively influences purchase intention (β = 0.381), and purchase intention positively influences purchasing decisions (β = 0.436). The R² values ​​were 0.893 for purchase intention and 0.935 for purchasing decisions. Purchase intention was found to significantly mediate the relationship between product quality/trust and purchasing decisions. These findings underscore the importance of enhancing product quality and trust as key strategies for driving purchase conversions on the Shopee digital platform.